2015
DOI: 10.1164/rccm.201411-2112ed
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension in Premature Infants. Sharpening the Tools of Detection

Abstract: measurements, as well as acceptable measurements in more than 1,000 children aged 5-12 years. A comparison of children living in a range of locations in India with those of Indian heritage who were living in London in the United Kingdom revealed significantly higher FEV 1 and FVC (per z-scores relative to reference values derived from Indian populations) in the London residents. However, when the India-resident children were subgrouped into urban, semiurban, and rural areas of residence, it was discovered that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
(20 reference statements)
1
14
0
1
Order By: Relevance
“…19,25,26 In this study we found a significant decrease in RV FWLS and IVS GLS in infants with BPD compared to infants without BPD (uncomplicated preterm infant), which remained significant after adjusting for the gestational age at birth, gender, and postnatal steroid use. In preterm infants with BPD, the magnitude of RV FWLS increased from 32 weeks to one year CA, but remained lower and tracked inferior when compared to infants without BPD by one-year CA, even when they no longer displayed clinical evidence of lung disease with oxygen requirement or respiratory support.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…19,25,26 In this study we found a significant decrease in RV FWLS and IVS GLS in infants with BPD compared to infants without BPD (uncomplicated preterm infant), which remained significant after adjusting for the gestational age at birth, gender, and postnatal steroid use. In preterm infants with BPD, the magnitude of RV FWLS increased from 32 weeks to one year CA, but remained lower and tracked inferior when compared to infants without BPD by one-year CA, even when they no longer displayed clinical evidence of lung disease with oxygen requirement or respiratory support.…”
Section: Discussionsupporting
confidence: 50%
“…As highlighted by Farrow et al, this observation suggests that a primary vascular injury coupled with RV dysfunction may occur in some extreme preterm infants, independent of the lung disease. 26 Although we only observed that one infant had echocardiographic signs of PH at one year CA, the infants with PH on their 36 week PMA echocardiograms that returned for a one-year CA follow-up (n=12 of 17, none of which required oxygen or respiratory support at one year CA ) still had decreased RV FWLS and IVS GLS and altered SLS base-to-apex pattern. Interestingly 25% (n=3) of the infants with PH at 36 weeks PMA that returned at one year CA did not carry a diagnosis of BPD and the patterns of altered strain mechanics persisted in this small sub-cohort as well.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…One of the implications of this report is that predicting which infants are at risk for the later development of BPD-PH very early in life (36) may be possible. This report underscores the need for screening for PH both early and late in the NICU course, as lung growth and vascular development are interdependent from the beginning of development.…”
Section: Evaluation Of Ph In the Premature Infant Populationmentioning
confidence: 93%